ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN SAFETY BEHAVIOR PADA PEKERJA BAGIAN LINE PRODUKSI DI PT COCA COLA BOTTLING INDONESIA - Angga Silahudin Novian Ramadhani; Bina Kurniawan; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Safe behavior is an act or acts of one or more labors to minimize the possibility of accidents. Based on the Activator-Behavior-Consequence (ABC) model, safe Behavior of labor can be influenced by activators and consequences. This study aims to analyze the relation between knowledge, motivation, implementation of work procedure (activator), positive reinforcement, and punishment (consequence) with implementation of safety behavior on workers in production section at PT Coca Cola Bottling Indonesia. The design was explanatory method with cross sectional approach. The population in this study is worker in line production section which amounted to 47 people. The sample of this study is taken from the total population. The study instrument used is a questionnaire with closed questions.  Statistical analysis use rank spearman test. Workers who behaved safely at 76.6%, good knowledge of safety behavior at 63.8%, adhere to work procedure at 53.2%, have high motivation at 51.1%, assume there are supportive positive reinforcement and punishment at 63.8% and 78.7%. Statistical analysis used is spearman rank correlation test. The results showed no relation between motivation (p = 0.679) with implementation of safety behavior. There is relation between knowledge (p = 0.003), implementation of work procedure (p = 0.007), positive reinforcement (p = 0.030) and punishment (p = 0.002) with implementation of safety behavior. The company should improve supervise role by supervisor to workers in following safety talk, and implementation of work procedure.  Provide rewards for workers as a form of appreciation and support in the form of incentives, and improve the role of supervisor by giving acknowledgement in the form of praise to workers who have behaved safely, and supervision of punishment to workers who do not behave safely.